2016
DOI: 10.5001/omj.2016.52
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Improves the Effects of Methotrexate in Patients with Active Rheumatoid Arthritis: Pilot Clinical Study

Abstract: Silibinin may improve the effects of MTX on certain biochemical and clinical markers of patients with active RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…These clinical observations are in line with the available data showing that resveratrol reduces pain, inflammation, and oedema, as well as articular destruction in experimental models of arthritis (Wang, Chen, Wang, 2016;Wang et al, 2017). Together with the previously reported data, the present finding supports the analgesic activity of dietary polyphenols in patients with mild-tomoderate knee pain, and suggests that it is in tune with the results of many pilot studies reported regarding the adjuvant use of polyphenols and other supplements during the treatment of inflammatory musculoskeletal disorders like knee OA and rheumatoid arthritis (Hussain et al, 2009;Hussain et al, 2016). Although the exact mechanism behind the impact of resveratrol on improving OA symptoms in a clinical setting has not been well described, a series of animal experiments conducted in the past few years has demonstrated that the oral administration of resveratrol is capable of significantly preventing the progression of osteoarthritis (Gu et al, 2016), and also exhibits a potent analgesic effect in different animal models (Wang et al, 2017;Bazzo et al, 2013).…”
Section: Discusionsupporting
confidence: 89%
“…These clinical observations are in line with the available data showing that resveratrol reduces pain, inflammation, and oedema, as well as articular destruction in experimental models of arthritis (Wang, Chen, Wang, 2016;Wang et al, 2017). Together with the previously reported data, the present finding supports the analgesic activity of dietary polyphenols in patients with mild-tomoderate knee pain, and suggests that it is in tune with the results of many pilot studies reported regarding the adjuvant use of polyphenols and other supplements during the treatment of inflammatory musculoskeletal disorders like knee OA and rheumatoid arthritis (Hussain et al, 2009;Hussain et al, 2016). Although the exact mechanism behind the impact of resveratrol on improving OA symptoms in a clinical setting has not been well described, a series of animal experiments conducted in the past few years has demonstrated that the oral administration of resveratrol is capable of significantly preventing the progression of osteoarthritis (Gu et al, 2016), and also exhibits a potent analgesic effect in different animal models (Wang et al, 2017;Bazzo et al, 2013).…”
Section: Discusionsupporting
confidence: 89%
“…No toxicity and adverse reaction were reported for silibinin in this trial (Hussain, Mortada, Jasim, & Gorial, 2016).…”
Section: Arthritismentioning
confidence: 69%
“…In a double‐blind clinical study, 30 males and 30 females with arthritis reheumatoid treated with methotrexate (12 mg/week) and silibinin (120 mg two times in a day) for 3 months. No toxicity and adverse reaction were reported for silibinin in this trial (Hussain, Mortada, Jasim, & Gorial, ).…”
Section: Safety and Adverse Reactions Of Oral Silymarin In Humansmentioning
confidence: 77%
“…Many consequences of inflammatory reactions, including oxidative stress and accelerated production of reactive oxygen species (ROS), can amplify the inflammatory response with consequent impact of increasing tissue damage and limited treatment outcomes [ 4 , 5 ]. Accordingly, the use of supplements from natural sources to attenuate the inflammation-induced oxidative damage, such as phytochemicals and trace elements, may provide further therapeutic benefits to the currently used antirheumatic agents [ 6 , 7 ]. Moreover, many of these natural supplements have the ability to potentially interfere with the inflammatory cascades, probably through attenuating the release of pro-inflammatory markers such as tumor necrosis factor-α (TNF-α) and other cytokines, which are clearly in many human and experimental animal studies [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%